Epidemiological investigation of a nosocomial outbreak of multidrug‐resistant Corynebacterium striatum at one Belgian university hospital. (15th April 2013) - Verroken, A.; Bauraing, C.; Deplano, A.; Bogaerts, P.; Huang, D.; Wauters, G.; Glupczynski, Y.; Allerberger, F.
Abstract During an 8‐month period, 24 Corynebacterium striatum isolates recovered from lower respiratory tract specimens of 10 hospitalized patients were characterized. The organisms were identified by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS) and by 16S rRNA gene sequencing. The cluster of C. striatum exclusively affected patients who had been admitted to an intensive care unit and/or subsequently transferred to one medium‐size respiratory care unit. Prolonged duration of hospitalization, advanced stage of chronic obstructive pulmonary disease, recent administration of antibiotics and exposure to an invasive diagnostic procedure were the most commonly found risk factors in these patients. Seven patients were colonized and three infected. All strains displayed a similar broad spectrum resistance to antimicrobial agents, remaining susceptible to vancomycin only. Typing analysis by MALDI‐TOF MS and by semi‐automated repetitive sequence‐based PCR (DiversiLab typing) showed that all outbreak‐associated C. striatum isolates clustered together in one single type while they differed markedly from epidemiologically unrelated C. striatum isolates. Pulsed‐field gel electrophoresis (PFGE) profiles revealed three distinct PFGE types among the C. striatum isolates associated with the outbreak while all external strains except one belonged to a distinct type. We conclude that C. striatum is an opportunistic nosocomial pathogen in long‐term hospitalized patients and can be at the origin of major outbreaks. The routine use of MALDI‐TOF MS greatly facilitated the recognition/identification of this organism in clinical samples and this technique could also offer the potential to be used as an easy and rapid epidemiological typing tool for outbreak investigation.